Mitochondrial DNA Corroborates the Genetic Variability of Clarias Catfishes (Siluriformes, Clariidae) from Cameroon - Shantanu Kundu; Piyumi S. De Alwis; Jerome D. Binarao; Soo-Rin Lee; Ah Ran Kim; Fantong Zealous Gietbong; Myunggi Yi; Hyun-Woo Kim (Life, 2023)
The airbreathing walking catfish (Clariidae: Clarias) comprises 32 species that are endemic to African freshwater systems. The species-level identification of this group is challenging due to their complex taxonomy and polymorphism. Prior to this study, the biological and ecological studies were restricted to a single species, Clarias gariepinus, resulting in a biased view of their genetic diversity in African waters. Here, we generated the 63-mitochondrial Cytochrome c oxidase subunit 1 (COI) gene sequences of Clarias camerunensis and Clarias gariepinus from the Nyong River in Cameroon. Both C. camerunensis and C. gariepinus species maintained adequate intra-species (2.7% and 2.31%) and inter-species (6.9% to 16.8% and 11.4% to 15.1%) genetic distances with other Clarias congeners distributed in African and Asian/Southeast Asian drainages. The mtCOI sequences revealed 13 and 20 unique haplotypes of C. camerunensis and C. gariepinus, respectively. The TCS networks revealed distinct haplotypes of C. camerunensis and shared haplotypes of C. gariepinus in African waters. The multiple species delimitation approaches (ABGD and PTP) revealed a total of 20 and 22 molecular operational taxonomic units (MOTUs), respectively. Among the two Clarias species examined, we found more than one MOTU in C. camerunensis, which is consistent with population structure and tree topology results. The phylogeny generated through Bayesian Inference analysis clearly separated C. camerunensis and C. gariepinus from other Clarias species with high posterior probability supports. The present study elucidates the occurrence of possible cryptic diversity and allopatric speciation of C. camerunensis in African drainages. Further, the present study confirms the reduced genetic diversity of C. gariepinus across its native and introduced range, which might have been induced by unscientific aquaculture practices. The study recommends a similar approach to the same and related species from different river basins to illuminate the true diversity of Clarias species in Africa and other countries.